Beyond Iraq and Afghanistan: Religion and Politics in United States War-Culture - Denton-Borhaug, Kelly (Dialog, 2012)
This article digs beneath the surface of American assumptions regarding war to explore the ethical interconnections between national identity, war, and religion. Striking differences emerge between the dynamics of religion and politics with regard to war and peace in presidential speeches regarding the Iraq and Afghanistan wars, and the analysis of war from an earlier generation, encapsulated by Dr. Martin Luther King Jr.'s “Beyond Vietnam: A Call to Conscience,” from 1967. Study of this political discourse helps us better understand our own reality in the United States, and the moral consequences of our beliefs about war, sacrifice, the human character, and the identity of the nation.